Investigation of low intensity light performances of kesterite CZTSe, CZTSSe, and CZTS thin film solar cells for indoor applications. Issue 29 (20th July 2020) - Park, Jongsung; Yoo, Hyesun; Karade, Vijay; Gour, Kuldeep Singh; Choi, Eunyoung; Kim, Moonyong; Hao, Xiaojing; Shin, So Jeong; Kim, JunHo; Shim, Hongjae; Kim, Dongmyung; Kim, Jong H.; et al.
Abstract : Three kesterite thin-film solar cells, Cu2 ZnSnSe4 (CZTSe), Cu2 ZnSn(S, Se)4 (CZTSSe), and Cu2 ZnSnS4 (CZTS), and based on low light intensity measurements, examined the possibility of using kesterite devices for indoor applications. Abstract : In this study, we prepared three kesterite thin-film solar cells, Cu2 ZnSnSe4 (CZTSe), Cu2 ZnSn(S, Se)4 (CZTSSe), and Cu2 ZnSnS4 (CZTS), and based on low light intensity measurements, examined the possibility of using kesterite devices for indoor applications. Interestingly, all the prepared cells exhibited nearly the same device efficiency under standard test conditions of 1 sun; however, under illumination with low-intensity halogen and LED lamps (200–400 lux), the power output of CZTSSe was twice that of CZTSe and CZTS. CZTSe (58%) and CZTS (37%) showed relatively larger open-circuit voltage drops than CZTSSe (29%). Suns– V oc measurements revealed that the ideality factor of CZTS and CZTSe increased as the light intensity decreased, which indicates severe recombination caused by deep-level defects at low light intensities. Furthermore, admittance spectroscopy measurements revealed that CZTSe and CZTS have deep trap energy levels, whereas CZTSSe has comparatively shallower trap energy levels; this validates the rapid open-circuit voltage drop under low light intensity conditions. Kelvin probe force microscopy measurements showed that CZTSSe exhibited a higher photovoltage (86 mV) under illumination at 400 lux compared with that under dark conditions. In addition, our results indicated that the CZTSSe sample showed relatively much higher charge separation at GBs (grain boundaries) owing to the downward band bending at the GBs. The findings revealed that for deeper energy levels, the open-circuit voltage reduction was faster; in addition, an absorber layer with shallower defects and efficient charge separation at the GBs can induce high power conversion efficiency under low-light conditions.